2008
DOI: 10.1163/22941932-90000187
|View full text |Cite
|
Sign up to set email alerts
|

Perforated Ray Cells in the Wood of Roots and Branches of Cerrado Species from Brazil

Abstract: Perforated ray cells (PRCs) are recorded here for the first time in the roots and branches of Schefflera vinosa, Caryocar brasiliense, Acosmium subelegans, Byrsonima basiloba, B. coccolobifolia, B. verbascifolia and Alibertia concolor which occur in Pratâniaʼs cerrado (SP, Brazil). PRCs are larger than normal ray cells, occurring isolated or in groups of two or more in the same ray, and are present predominantly in the uniseriate portion of multiseriate rays in all species studied. In the roots and branches, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
1
7
1
1
Order By: Relevance
“…It is unique within the family because of its very scanty axial parenchyma, making it similar mainly to Byrsonima , which can also have a shrub habit (Solereder1908, Metcalfe and Chalk 1950). However, Byrsonima has shorter radial vessel chains, the rays are wider and heterocellular with body procumbent and square to upright marginal cells (Sonsin et al 2014), as opposed to Mcvaughia , which has heterocellular mixed rays. Byrsonima also has abundant septate fibers, which are absent in Mcvaughia .…”
Section: Discussion On the Anatomical Charactersmentioning
confidence: 99%
“…It is unique within the family because of its very scanty axial parenchyma, making it similar mainly to Byrsonima , which can also have a shrub habit (Solereder1908, Metcalfe and Chalk 1950). However, Byrsonima has shorter radial vessel chains, the rays are wider and heterocellular with body procumbent and square to upright marginal cells (Sonsin et al 2014), as opposed to Mcvaughia , which has heterocellular mixed rays. Byrsonima also has abundant septate fibers, which are absent in Mcvaughia .…”
Section: Discussion On the Anatomical Charactersmentioning
confidence: 99%
“…Divergences regarding the delimitation of growth layers in C. brasiliense have been observed in the literature, such as the occurrence of discontinuous bands and lines of axial parenchyma (Voigt et al 2010;Sonsin et al 2014) and the presence of fibrous zones (Gonçalves 2010;Sonsin-Oliveira 2010). Regarding axial parenchyma, Voigt (2010) mentions a tendency for a reticulate pattern, while Gonçalves (2010) observes vasicentric parenchyma.…”
Section: Bioresourcescommentioning
confidence: 99%
“…Development of perforated ray cells takes place due to variable cambial activity and is not a constant anatomical feature; therefore it is of little taxonomic value (Carlquist 1988). Sonsin et al (2008) isolated or groups of perforated ray cells in seven species of Cerrado forest of Brazil. Their study demonstrated structural variations in the branches and roots of these species and concluded that occurrence of perforated ray cells in non-related families is not a diagnostic feature and does not bear any phylogenetic value.…”
Section: Structure Of the Included Phloem Islandsmentioning
confidence: 99%